Pengaruh Struktur Aset, Kebijakan Dividen, Pertumbuhan Penjualan dan Ukuran Perusahaan Terhadap Kebijakan Hutang - Nurjanah, Siti; Zulaecha, Hesty Ervianni; Hamdani, Hamdani; Pambudi, Januar Eky (Universitas Gajah Putih, 2022)
The purpose of this study was to determine the effect of managerial ownership, ios, and leverage on earnings quality in consumer goods industry companies listed on the Indonesian stock exchange. The research time period used is 4 years, namely the 2016-2021 period. The population of this study includes all companies listed on the Indonesia Stock Exchange for the 2016-2021 period. The sampling technique used purposive sampling technique. Based on the predetermined criteria obtained 12 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis using the eviews 10 . data processing program.The results showed that managerial ownership had a positive effect on earnings quality, while ios and leverage had no effect on earnings quality.